Legal Reformulation of Religious Court Divorce Decisions in Indonesia Due to Religious Conversion (Apostasy) Based on Unification and Principles of Islamic Law Formation - Syaiful Annas; M. Fahmi Al-Amruzi; Gusti Muzainah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Religious Courts as a manifestation of Islamic justice is reflected in its decisions that make Islamic law (fiqh) as a reference to its legal considerations. The difference in opinion of fiqh scholars regarding the application of divorce mechanisms due to the religious conversion of one of the parties, has implications for the birth of disparities in religious court decisions due to the absence of legal unification so as not to guarantee the realisation of justice, certainty and legal expediency in the decision. This research aims to explore and analyse the disparity in religious court decisions and to reformulate the law that is more appropriate in applying the divorce mechanism due to the religious conversion of one of the parties. This research is normative legal research, which is qualitative and uses a philosophical approach. The importance of legal unification so that there is no disparity in decisions will ensure the realisation of justice, certainty, and expediency, Moreover, religious court decisions as a manifestation of Islamic judicial decisions will become law for the community, therefore, it must also consider the principles in the formation of Islamic law